2003
DOI: 10.1677/joe.0.1770471
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole-induced hypothyroidism in rats ameliorates oxidative injury in experimental colitis

Abstract: Depression of metabolism by hypothyroidism decreases oxidant production and thus protects tissues against oxidant damage. Moreover, it is well-known that abnormal gut motility is a common manifestation in hypo/ hyperthyroidism. In this study, we aimed to investigate the putative beneficial effects of methimazole on oxidative injury and dysmotility in a rat colitis model. Methimazole (0·04%) was administered in drinking water starting 15 days prior to induction of colitis. Colitis was induced by intracolonic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 24 publications
1
26
0
14
Order By: Relevance
“…These observations corroborate with the earlier reports, where free radical scavenging property of PQQ has been highlighted (Misra et al, 2004;Shrivastava et al, 2010).With other two concentrations of PQQ (1 and 5 mg /kg) also, LPO was inhibited in the tissues of all the studied organs, with a significant elevation in SOD and CAT. Some workers suggest that hypothyroidism protects tissues against accelerated lipid peroxidation, although the data concerning oxidation / antioxidation in hypothyroidism are incomplete and contradictory (Isman et al, 2003;Venditti and Di Meo, 2006). In fact, Dariyerli et al, (2004) did not find any change in the content of malondialdehyde in rats with thiamizoleinduced hypothyroidism.…”
Section: Discussionmentioning
confidence: 97%
“…These observations corroborate with the earlier reports, where free radical scavenging property of PQQ has been highlighted (Misra et al, 2004;Shrivastava et al, 2010).With other two concentrations of PQQ (1 and 5 mg /kg) also, LPO was inhibited in the tissues of all the studied organs, with a significant elevation in SOD and CAT. Some workers suggest that hypothyroidism protects tissues against accelerated lipid peroxidation, although the data concerning oxidation / antioxidation in hypothyroidism are incomplete and contradictory (Isman et al, 2003;Venditti and Di Meo, 2006). In fact, Dariyerli et al, (2004) did not find any change in the content of malondialdehyde in rats with thiamizoleinduced hypothyroidism.…”
Section: Discussionmentioning
confidence: 97%
“…The results concerning TAS revealed that chronic administration of methimazole stimulated protection against free radicals. Such conclusions, based on the previous analyses, have already been presented (16,32), although it is still a matter of debate (26).…”
Section: Resultsmentioning
confidence: 68%
“…Hypothyroidism lowers tissue oxygen demand and is associated with the decreased production of free oxygen radicals. It also protects tissues against lipid peroxidation, stimulating the mechanisms of the antioxidant system (16,23,35). Methimazole is an anti-thyroid drug commonly used around the world in the long-term treatment of hyperthyroidism in humans (11,15,27,39), dogs (37), and cats (12,13,18,24,25,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…тика мерказолілу ("Здоров'я", Україна) в дозі 25 мг/кг протягом 21-ї доби [14]. Контроль здій-снювали за рівнем тироксину, трийодтироніну і тиреотропного гормону, а також за масою тварин і їх руховою активністю.…”
unclassified